A weekly session of jumping interval training effectively enhances aerobic, anaerobic, and jumping performance in aerobic gymnastics - Ma, D.; Wang, K.; Silva, R. M.; Xu, Q.; Zhao, Z. (Journal of Human Kinetics, 2025)
This study aimed to compare the impact of varying weekly frequencies of jumping interval training (JIT) on aerobic and anaerobic fitness, as well as jumping abilities of youth female athletes specialized in aerobic gymnastics. A randomized controlled study design was conducted spanning 8-week duration, involving 69 youth female athletes (16.3 ± 1.2 years) specialized in aerobic gymnastics. Participants were allocated into two experimental groups: JITw1 (comprising individuals subjected to JIT once a week), and JITw2 (encompassing individuals undergoing JIT twice a week), alongside a control group. Prior to and post the intervention period, athletes underwent evaluations of their performance through the countermovement jump test (CMJ), a specialized anaerobic assessment personalized for aerobic gymnasts (SAGAT), and a 20-m multistage fitness test. A mixed ANOVA was conducted for statistical analysis. Significant time (baseline and post-intervention) x group (JITw1, JITw2 and control) interactions were found in the SAGAT (p < 0.001), the CMJ (p < 0.001) and the 20-m multistage fitness test (p < 0.001). Post-intervention analysis revealed significantly lower scores in the SAGAT for the control group compared to the JITw2 group (p = 0.003). Significantly higher scores were observed for the JITw2 group in the CMJ test compared to the control group (p = 0.001). Significantly lower scores in the 20-m multistage fitness test were found in the control group compared to the JITw2 and JITw1 groups (both p < 0.001). As conclusion, while additional JIT training once a week may suit for minimal effective training and positive adaptations, training twice a week is advisable when significant improvements are desired.